Meningkatkan Motivasi Masyarakat Terhadap Kesadaran Gotong Royong - Alfian; Anis Kurlillah; Safwan Kamal; Fakhrizal; Munadiati (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2023)
Mutual cooperation is an activity that can reflect activities that are beneficial to other people. Therefore, the lack of public awareness in mutual cooperation activities can be a serious problem for building a society that cares about the environment. The location of this service is in Afdeling II Bukit Village, Aceh Province. The aim of this service is to increase community motivation towards mutual cooperation awareness in an effort to create community participation and create a healthy, clean and comfortable environment. The method used in this activity is a method of socialization regarding the importance of awareness of community participation in working together to create cleanliness and beauty of the surrounding environment. The real result of carrying out this service activity is that it can produce work in the form of installing signs with the names of Allah's obligatory attributes and hanging flower pots installed along the roads to create the beauty of the village. Apart from that, the community's sense of concern for the environment can grow and they can adapt further to routine habits of protecting the environment to help develop healthy, clean and comfortable villages.